Money and Uncertainty of Outcome in Modern Sports Based on the Example of Football - Metelski, Adam (Acta Universitatis Lodziensis. Folia Oeconomica, 2024)
One of the fundamental aspects of professional football is competition, which not only captivates fans but also drives its economic success. Money undeniably plays a significant role in determining sports outcomes, as clubs with larger budgets often possess better players. This article aims to examine the relationship between the market value of football clubs’ squads and their performance in the top 15 European leagues, as per the UEFA ranking. Among these leagues, Manchester City boasts the highest players market value in Europe, estimated at 1,110 million EUR, accounting for a mere 11.21% of the total market value of all English Premier League players. In summary, over the course of the last five seasons, out of 75 possible champions across the analysed leagues, the team with the most expensive squad has emerged victorious on 54 occasions. Consequently, it prompts consideration as to whether any measures should be taken to foster greater balance and to reduce the domination of wealthy teams in national football leagues.